2017
DOI: 10.1055/s-0037-1607427
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Knee Arthroplasty with Metaphyseal Sleeves without Stem: Short-Term Results

Abstract: Purpose  The aim of this study was to evaluate the efficacy of revision total knee arthroplasty (TKA) with cementless metaphyseal sleeves without stems either in the femoral or tibial side or in both. Methods  In this retrospective study, 51 patients (51 knees) operated in the period 2010 to 2015 met the above-mentioned criteria and were invited to a medical examination including X-rays. Forty-six were available for the study. Mean follow-up was 37 months. Knee Society score (KSS) (objective knee score), West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…To the best of our knowledge, ours is the first report on the use of MS in RKA of Arabic patients. The female predominance in our cohort has been observed in other series and was attributed to postmenopausal osteoporosis [ 31 , 32 ]. We believe that this is a reflection of the higher percentage of primary TKA in our female patients as compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…To the best of our knowledge, ours is the first report on the use of MS in RKA of Arabic patients. The female predominance in our cohort has been observed in other series and was attributed to postmenopausal osteoporosis [ 31 , 32 ]. We believe that this is a reflection of the higher percentage of primary TKA in our female patients as compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…13,36 The current literature surrounding optimal stem use in rTKA, let alone TM Cone utilizing rTKA, is poor. 37 MS implants without long stems have shown mixed results; Stefani et al 38 and Fonesca et al 39 reported favourable outcomes whereas Gøttsche et al 40 encountered problems with implant malalignment. In contrast, TM cones without long stems have demonstrated consistently promising outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The TC3 implant (Depuy Synthes) has been used for many years as both a primary and revision implant with good clinical results in short-term [13][14][15][16][17] and long-term [18] observation. Damage of the prosthesis at the level of stem -condyle junction is a rare phenomenon, but it is described in the literature and carries serious consequences for the patient [6].…”
Section: Discussionmentioning
confidence: 99%